Structural characterisation of the HT3 motif of the polyhistidine triad protein D from Streptococcus pneumoniae. Issue 13 (14th June 2018) - Luo, Zhenyao; Pederick, Victoria G.; Paton, James C.; McDevitt, Christopher A.; Kobe, Bostjan
Abstract : The bacterium Streptococcus pneumoniae (the pneumococcus) is a major human pathogen that requires Zn 2+ for its survival and virulence in the host environment. Polyhistidine triad protein D (PhtD) has a known role in pneumococcal Zn 2+ homeostasis. However, the mechanistic basis of PhtD function remains unclear, partly due to a lack of structural information. Here, we determined the crystal structure of the fragment PhtD 269‐339, containing the third Zn 2+ ‐binding histidine triad (HT) motif of the protein. Analysis of the structure suggests that Zn 2+ binding occurs at the surface of the protein and that all five HT motifs in the protein bind Zn 2+ and share similar structures. These new structural insights aid in our understanding of how the Pht proteins facilitate pneumococcal Zn 2+ acquisition. Abstract :